2001
DOI: 10.1159/000048095
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Fertility in Adult Females and Males with Congenital Adrenal Hyperplasia

Abstract: Female patients with classic 21-hydroxylase deficiency (21-OHD) present with decreased fertility and low childbirth rates, women with a salt-wasting form of 21-OHD being most severely affected. In cases of undersubstitution with glucocorticoids, tonic androgen secretion disturbs ovulation. However, even adequately substituted females may present with apparent infertility. Despite adrenal androgen suppression, adrenal progesterone secretion can prevent thickening of the endometrium in the follicular phase. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Yet in the small cohort studies of males with C-21-OHD who have markedly increased adrenal androgen levels (19)(20)(21)(22), infertility was limited to those with testicular adrenal rests. In addition, a small Finnish study reported that males with 21-OHD had similar levels of gonadotropins and inhibin B to age-matched controls (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet in the small cohort studies of males with C-21-OHD who have markedly increased adrenal androgen levels (19)(20)(21)(22), infertility was limited to those with testicular adrenal rests. In addition, a small Finnish study reported that males with 21-OHD had similar levels of gonadotropins and inhibin B to age-matched controls (22).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of males treated with large doses of exogenous testosterone combined with progesterone have reported findings of suppressed gonadotropin levels and spermatogenesis and consequent oligospermia (18). Accordingly, it has been speculated that the infertility associated with untreated CAH in men might be attributable to overproduction of adrenal androgens, leading to suppressed gonadotropin secretion and a hypogonadotropic state (19). However, the reported data on fertility in males with CAH are conflicting (20)(21)(22).…”
mentioning
confidence: 99%
“…Current replacement treatment (glucocorticoids) does not precisely replicate the circadian rhythm of cortisol secretion because it lacks the close temporal relationship to adrenocorticotropin (ACTH) pulses, and increased adrenal activity will continue despite treatment. Increasing treatment doses to achieve satisfactory androgen suppression exposes the patient to the negative effects glucocorticoids have on growth, explaining why some ‘well-controlled’ CAH patients may experience early puberty, compromised final height, polycystic ovarian disease, and male infertility [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…From the beginning of the 20th century, intersexuality has been recognized by modern Western medicine as a medical condition, a disorder of sex development, requiring life-long medical treatment, with genital abnormalities being corrected by surgery to allow so-called normal sexual function [1]. Corrective genital surgery is guided by cosmetic appearance and sexual functionality of the external genitalia, but often does not allow local sexual sensations and feelings [2,3,4,5]. Certain advocacy groups even complain that Western society would force individuals with disorders of sex development to conceal their status and make them choose either a male or female role, whereas other (non-Western) societies consider their condition special, and give them a special gender role often associated with high social status [6, 7].…”
Section: Introductionmentioning
confidence: 99%